Kinetic Sculpture - Witabora, Joneta; Witabora, Jonata (Bina Nusantara University, 2014)
Kinetic Sculpture was born from a long process of searching new approach in sculpture. The artists tried to escape from 'static' paradigm and tried to implement movement into their works: a sculpture that is mobile. Movement is always a fascinating phenomenon to eyes. Kinetic sculpture strength lies in its unique character in combining science and art. Kinetic Sculptures are really interesting pieces of art. It succeeds to fascinate human everytime.